2015
DOI: 10.1200/jco.2015.63.4238
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Fluorouracil, Leucovorin, and Oxaliplatin in Stage II to III Colon Cancer: Updated 10-Year Survival and Outcomes According to BRAF Mutation and Mismatch Repair Status of the MOSAIC Study

Abstract: The OS benefit of oxaliplatin-based adjuvant chemotherapy, increasing over time and with the disease severity, was confirmed at 10 years in patients with stage II to III colon cancer. These updated results support the use of FOLFOX in patients with stage III disease, including those with dMMR or BRAF mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
440
3
16

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 576 publications
(469 citation statements)
references
References 31 publications
10
440
3
16
Order By: Relevance
“…Andre et al and colleagues in an analysis of the Multicenter International Study of Oxaliplatin/5-Fluorouracil/Leucovorin in the Adjuvant Treatment of Colon Cancer (MOSAIC) study evaluated MMR status in 986 of the 2240 enrolled patients. A DFS benefit from FOLFOX compared with 5-FU alone was observed in a small number of patients with dMMR CRC (Andre et al, 2015). Moreover, a recent study involving 433 dMMR stage-II and stage-III tumours found that adjuvant FOLFOX improved DFS compared to 5-FU alone, with the benefit limited to stage-III tumours and to sporadic cases only (Tougeron et al, 2016).…”
Section: Msi As a Prognostic Marker With Adjuvant 5-fu Plus Oxaliplatmentioning
confidence: 99%
See 2 more Smart Citations
“…Andre et al and colleagues in an analysis of the Multicenter International Study of Oxaliplatin/5-Fluorouracil/Leucovorin in the Adjuvant Treatment of Colon Cancer (MOSAIC) study evaluated MMR status in 986 of the 2240 enrolled patients. A DFS benefit from FOLFOX compared with 5-FU alone was observed in a small number of patients with dMMR CRC (Andre et al, 2015). Moreover, a recent study involving 433 dMMR stage-II and stage-III tumours found that adjuvant FOLFOX improved DFS compared to 5-FU alone, with the benefit limited to stage-III tumours and to sporadic cases only (Tougeron et al, 2016).…”
Section: Msi As a Prognostic Marker With Adjuvant 5-fu Plus Oxaliplatmentioning
confidence: 99%
“…In prospectively col- (Andre et al, 2015;Gavin et al, 2013;Guastadisegni et al, 2010;Klingbiel et al, 2015;Popat et al, 2005;Roth et al, 2012;Sinicrope et al, 2015). lected tumor tissue MSI was detected in 314 of 2580 stage-III CRCs and was prognostic overall for time to relapse (TTR), but not for DFS or OS (Sinicrope et al, 2013a).…”
Section: Msi As a Biomarker With Cetuximab Adjuvant Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Results were consistent between both firstBline trials, independent of chemotherapy strategy and other standard prognostic factors. OxFU is a commonly used firstBline therapy in aCRC, and was the firstBline regimen used in the majority of patients analysed herein, and indeed oxaliplatin may provide particular benefits in Bmutant patients [3,21] .…”
Section: " ! And!! $mentioning
confidence: 99%
“…Defektes MMR (dMMR) wurde bei 9,4 % der Studienpopulation nachgewiesen. Unter FOLFOX4 konnte kein signifikant verbesser-tes Überleben in der dMMR-Gruppe (Stadium II/III) nachgewiesen werden (HR 0,41; 95 % CI:0,16 -1,07) [886].…”
Section: Level Of Evidence 1aunclassified